2007
DOI: 10.1017/s1368980007687138
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of high vitamin A supplementation coverage among pre-school children in Mali: the National Nutrition Weeks experience

Abstract: Objectives: To assess vitamin A supplementation (VAS) coverage of children aged 6 -59 months and the factors that favour or limit this coverage during the National Nutrition Weeks in Mali. Design: Cross-sectional study. Interviews about demographic factors and children's adherence to the vitamin A capsule distribution programme were conducted. Professionals' knowledge of vitamin A and various aspects related to the supplementation strategy were assessed. Setting: Five regions out of the eight regions in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 9 publications
1
34
0
Order By: Relevance
“…Yet little is known about predictors for their practices at the individual level (in this study, we define household, maternal and child-level characteristics as ‘individual’ characteristics of a child, as they affect each child uniquely in their combination). Existing studies focus mainly on identifying local or regional-level characteristics of their practice3–14: a comparatively larger body of evidence is available for the Nigerian setting (eg, Begum et al 3 for iron–folic acid supplementation, Odusanya et al 4 and Adeloye et al 6 on vaccination coverage and Ogbo et al 8 on breast feeding). Haile et al 9 and Belew et al 13 investigate vitamin A supplementation (VAS) and dietary diversity and meal frequency, respectively, in Ethiopia (or its subregions).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet little is known about predictors for their practices at the individual level (in this study, we define household, maternal and child-level characteristics as ‘individual’ characteristics of a child, as they affect each child uniquely in their combination). Existing studies focus mainly on identifying local or regional-level characteristics of their practice3–14: a comparatively larger body of evidence is available for the Nigerian setting (eg, Begum et al 3 for iron–folic acid supplementation, Odusanya et al 4 and Adeloye et al 6 on vaccination coverage and Ogbo et al 8 on breast feeding). Haile et al 9 and Belew et al 13 investigate vitamin A supplementation (VAS) and dietary diversity and meal frequency, respectively, in Ethiopia (or its subregions).…”
Section: Introductionmentioning
confidence: 99%
“…Haile et al 9 and Belew et al 13 investigate vitamin A supplementation (VAS) and dietary diversity and meal frequency, respectively, in Ethiopia (or its subregions). Ayoya et al 7 contribute evidence on vitamin A supplementation coverage in Mali, Bendech et al 10 on the same indicator in Guinea, Chirawurah et al 12 on iodised salt usage in rural north Ghana and Mutua et al 14 on immunisation coverage in Nairobi, Kenya. Whenever data are being pooled, it is not done so consequently for the entire Sub-Saharan African (SSA) region or its subregions West, Central, East and Southern Africa—for example, Janmohamed et al 5 pool data from 13 SSA countries to investigate VAS and its determinants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the pattern of VAC supplementation program coverage is important for improving the health outcome of children and their survival. Although numerous studies in sub-Saharan Africa [22,23,24] and globally [25,26,27,28] have examined and documented disparities in coverage of VAC supplementation based on individual characteristics, the influence of neighborhoods and the socioeconomic characteristics on coverage of VAC supplements has received less attention, whereas contextual characteristics of neighborhoods where these children reside may in themselves constitute a major disadvantage. For instance, it has been shown that residents of socioeconomically disadvantaged communities tend to have a higher mortality risk regardless of their individual demographic and socioeconomic characteristics [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study in Mali found that vitamin A supplementation coverage during the SIAN was increased by using traditional communication channels [14], so this should be considered in future SIAN social mobilization plans. In the current study, prior participation in nutritional education activities was associated with greater participation in the SIAN, although it is conceivable that caregivers who participated in educational programs were those who were more motivated in general and therefore would have been more likely to utilize nutritional screening services anyway.…”
Section: Discussionmentioning
confidence: 99%